The Sustainability Pension Sub-Index in the Context of the Indicators Weights - Jolana Gubalová; Petra Medveďová; Jana Špirková (Statistika: Statistics and Economy Journal)
Pension systems are sensitive to economic and demographic challenges. The sustainability sub-index is essential for ensuring the stability and reliability of pension systems for both current and future pensioners. It assists policymakers and stakeholders in identifying areas where reforms may be necessary to enhance the sustainability of pension policies. This contribution focuses on determining the weights for individual indicators of the sustainability sub-index using several methods of weight determination in multi-criteria decision-making, specifically subjective methods. The weights are determined using four methods: Saaty’s exact and approximate method, Thurstone's method of pair comparison, and Best-Worst method. It also provides sustainability sub-index values for selected European countries included in Mercer’s score determination, as well as for Slovakia, which is not yet included in Mercer’s evaluations. Thurstone's method of pair comparison appears to be the method most consistent with Mercer's methodology in determining the weights for indicators of the sustainability sub-index.